The Oxford handbook of organizational change and innovation - Poole, Marshall Scott, 1951-; Van de Ven, Andrew H., (Oxford handbooks online., 2021)
Organizational change and innovation are central and enduring issues in management theory and practice. Dramatic changes in population demographics, technology, competitive survival, and social, economic, and environmental health and sustainability concerns means the need to understand how organizations repond to these shifts through change and innovation has never been greater. Why and what organizations change is generally well known; how organizations change is therefore the central focus of this handbook. It focuses on processes of change - or the sequence of events in which organizational characteristics and activities change and develop over time - and the factors that influence these processes, with the organization as the central unit of analysis.